Evaluation of Clinical Findings, Optical Coherence Tomography, Fundus Fluorescein Angiography, and Indocyanine Green Angiography Imaging in Patients with Polypoidal Choroidal Vasculopathy - Ruveyde Garip (Beyoglu Eye Journal, 2020)
INTRODUCTION[|]The aim of this study was to describe clinical findings as well as spectral-domain optical coherence tomography (SD-OCT), fundus fluorescein angiography (FA), and indocyanine green angiography (ICGA) findings of polypoidal choroidal vasculopathy (PCV).[¤]METHODS[|]This retrospective, observational case series included 144 eyes of 103 patients who were diagnosed with PCV between January 2014 and August 2016. Best corrected visual acuity, 90-diopter lens slit-lamp fundus biomicroscopy examination findings, color fundus photography, SD-OCT, FA, and ICGA findings were evaluated at the time of diagnosis.[¤]RESULTS[|]Sixty-six patients (93 eyes, 64.1%) were male and 37 (51 eyes, 35.9%) were female. Sixty-two (60.2%) patients had unilateral involvement. The most common SD-OCT finding was retinal pigment epithelial detachment (PED). Red-orange subretinal lesions were seen in 20 eyes (13.9%). There was a single polyp in 21 (14.6%) eyes, and more than 1 polyp in 123 (85.4%) eyes observed with ICGA imaging. The polyps were located in the peripapillary area in 10 (6.9%) eyes, the macular area in 91 (63.2%) eyes, and the extramacular area in 1 (0.7%) eye. A significant branching vascular network was seen in the ICGA images of 112 (77.8%) eyes.[¤]DISCUSSION AND CONCLUSION[|]In this study, the majority of patients were male, with unilateral macular polyps. A serous PED and an exudative pattern were the most common clinical manifestations. SD-OCT showed specific findings for PCV, but ICGA was the most useful test for diagnosis.[¤]